1968
DOI: 10.2135/cropsci1968.0011183x000800040014x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Orchardgrass (Dactylis glomerata L.) to Different Light and Temperature Environments. II. Leaf Age and Photosynthetic Activity1

Abstract: The variation in rate of apparent photosynthesis (PR) with leaf age in three populations of orchardgrass, grown in two different temperature environments, was investigated using a Warburg manometric technique. Fully expanded leaves maintained a high PR for 15 to 20 days but the rate rapidly declined thereafter. PR (oxygen evolution) per unit leaf area closely paralleled the synthesis and degradation of the chlorophyll pigments; PR per unit chlorophyll changed very little throughout the life of the leaf. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
2

Year Published

1969
1969
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
2
18
0
2
Order By: Relevance
“…2D). Treharne et al (1968) also found that leaf chlorophyll content in cocksfoot decreases with age. Treharne & Eagles (1970) reported a fall of 60% in RuBisCO activity of the youngest fully expanded cocksfoot leaves after 30 days' full expansion at 25°C.…”
Section: Physiological Changes With Leaf Agementioning
confidence: 82%
See 2 more Smart Citations
“…2D). Treharne et al (1968) also found that leaf chlorophyll content in cocksfoot decreases with age. Treharne & Eagles (1970) reported a fall of 60% in RuBisCO activity of the youngest fully expanded cocksfoot leaves after 30 days' full expansion at 25°C.…”
Section: Physiological Changes With Leaf Agementioning
confidence: 82%
“…For grasses, the negative effect of leaf age on leaf photosynthesis in different positions on one tiller, and during ageing of leaves in a particular position on the tiller, has previously been reported (e.g., Jewiss & Woledge 1967;Treharne et al 1968;Treharne & Eagles 1970;Woledge 1972;Robson & Parsons 1978). …”
Section: Response Of Photosynthesis To Regrowth Durationmentioning
confidence: 83%
See 1 more Smart Citation
“…However, a slow, steady decline of photosynthesis per unit chlorophyll led Treharne et al (1968) to suggest that the peak of photosynthetic efficiency was at, or just before, the period of most rapid leaf expansion, and that there was a gradual deterioration with leaf age. From the present results, it appears that the differences in chlorophyll between successive leaves observed by Treharne et al (1968) may have reflected a difference in mesophyll cell size (Table 3). The present results also indicate that lower leaves, which are more efficient in the use of CO2 than the upper leaves, might often be shaded by less efficient leaves while still capable of maximum response to light.…”
Section: Discussionmentioning
confidence: 99%
“…Après l'expansion totale de la feuille, un haut niveau de photosynthèse est maintenu pour 15 à 20 jours. Par la suite, le taux de photosynthèse diminue rapidement (Treharne et al 1968). Jung et Baker (1985) ont mentionné qu'il y avait peu d'avantage au point de vue production à espacer les coupes de plus de 35 à 42 jours.…”
unclassified